2020
DOI: 10.1007/s11912-020-00934-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cancer: a Comprehensive Review

Abstract: Purpose of Review The outbreak of the novel coronavirus disease 2019 has emerged to be the biggest global health threat worldwide, which has now infected over 1.7 million people and claimed more than 100,000 lives around the world. Under these unprecedented circumstances, there are no well-established guidelines for cancer patients. Recent Findings The risk for serious disease and death in COVID-19 cases increases with advancing age and presence of comorbid health conditions. Since the emergence of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
259
0
36

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(305 citation statements)
references
References 100 publications
10
259
0
36
Order By: Relevance
“…Preliminary reports suggest that patients with an underlying malignancy have inferior outcomes. [3][4][5][6][7] While haematology patients are thought to be at increased risk of developing severe complications both due to immune dysfunction from their underlying haematological disorder and immunosuppressive therapies used for treatment, [8][9][10] delays in treatment of the underling malignancy may compromise patient safety and survival. Data from other cohorts worldwide suggest mortality from COVID-19 is higher in haematology patients compared to the general population, 3,11,12 with reported mortality rates between 39% and 50% in other British haematology patient cohorts.…”
mentioning
confidence: 99%
“…Preliminary reports suggest that patients with an underlying malignancy have inferior outcomes. [3][4][5][6][7] While haematology patients are thought to be at increased risk of developing severe complications both due to immune dysfunction from their underlying haematological disorder and immunosuppressive therapies used for treatment, [8][9][10] delays in treatment of the underling malignancy may compromise patient safety and survival. Data from other cohorts worldwide suggest mortality from COVID-19 is higher in haematology patients compared to the general population, 3,11,12 with reported mortality rates between 39% and 50% in other British haematology patient cohorts.…”
mentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 has a ten times higher a nity to ACE2 compared to SARS-CoV, which is consistent with the higher e ciency of infection of SARS-CoV-2 [11]. While no cure has currently been found, several clinical trials are being performed to determine what the most e cacious treatment regimen is for COVID-19, with an extensive list of potential therapies detailed in a review by Gosain et al [12]. Currently, patient management involves supportive treatment and measures to prevent further spread of the virus [13].…”
Section: Introductionmentioning
confidence: 84%
“…COVID-19 marks the emergence of the third large-scale epidemic related to the coronavirus, after SARS-CoV in 2002 and Middle-East respiratory syndrome coronavirus (MERSCoV) in 2012. [ 6 ] World Health Organization (WHO) declared the epidemic as a high-risk Public Health Emergency of International Concern (PHEIC). [ 7 , 8 ] Severe cases of COVID-19 can lead to heart, and respiratory failure, acute respiratory syndrome, or even death.…”
Section: Introductionmentioning
confidence: 99%